ANALISIS DAYA SAING KOMODITI EKSPOR NON – MIGAS INDONESIA DI PASAR INTERNASIONAL (studi kasus pada 3 komoditi non – migas tahun 2013 – 2020) - Sutan Sholahudin Iqbal; Khusaini, Moh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Indonesia has natural resources that can encourage the economy, one of which is by carrying out export activities. However, Indonesia's exports, especially in the non-oil and gas sector, only grew by 1% in the period 2013 - 2020. For this reason, in the non-oil and gas sector there are commodities that have the potential to increase exports, including Coffee, Frozen Shrimp and Coal. In international trade, there are several competing countries for these commodities, so strong competitiveness is needed to survive in the international market. This study aims to see the extent to which Indonesia has competitiveness in the international market and what factors affect the growth of the export commodities studied. The results of this study are expected to be a suggestion for the government to determine the right policies to increase Indonesia's exports, especially in the non-oil and gas sector. This study uses the Revealed Comparative Advantage (RCA) method to see how strong the competitiveness is and Constant Market Share (CMS) to see the factors that affect the growth of the export commodities studied. The results of this study indicate that the three commodities studied, namely Coffee, Frozen Shrimp and Coal, have strong competitiveness in the international market.